PENGARUH KONSENTRASI POLIETILEN GLIKOL DAN LAMA PENYIMPANAN TERHADAP VIABILITAS BENIH KAWISTA - Murrinie, Endang Dewi; Arini, Nindya; Nurhayati, Tafiz Rizka (Fakultas Pertanian Universitas Janabadra, 2025)
Wood apple (Feronia limonia (L.) Swingle) plants are currently classified as rare and endangered, so they require the development of new plant populations. Wood apple plants only bear fruit once a year, with seed harvest time ranging from 8-9 months after anthesis; therefore, seeds are not available throughout the year. To ensure the availability of wood apple seeds, it is necessary to store them, but stored seeds generally decrease in viability due to chemical changes that occur within the seeds. The study aimed to determine the effect of polyethylene glycol (PEG) concentration and storage time on the viability of wood apple seeds. The study was a factorial experiment consisting of two factors using a complete random design that was repeated three times. The first factor is the concentration of PEG, which consists of four levels: 0%, 20%, 40%, and 60%. The second factor is that the storage length consists of three levels, namely 0, 12, and 18 months. The data from the study were analyzed and further tested using Duncan's Multiple Range Test at a 5% significance level. The results showed that the concentration of polyethylene glycol had an effect on the percentage and rate of germination of wood apple seeds, but had no effect on the growth of germination. The storage time does not affect the percentage and rate of germination, but it does affect the growth of germination. Wood apple seeds stored for longer than 12 months exhibit declining sprout growth.